Balancing Coffee Kit Assembly Line: a Case Study of a Sample Factory - Yamphuan, Paiboon (Srinakharinwirot University Engineering Journal, 2018)
This research aims to increase productivity of the coffee kit assembly process of a case study. The procedure are as following: production recording, analyzing and improving, new jobs balancing and new working methods designing by using techniques of ECRS (Eliminate, Combine, Rearrange, Simplify), line balancing techniques and motion study. They were used in real production and performance was measured for process improvements. The results obtained from the recording and analysis of data were found that there were 13 stations of coffee kit making process, straight line, and each step took very different time. This has resulted in some waiting stations and loss of production. There were 24 workers in manual coffee assembly line which was unsuitable. A processing time (takt time) took 1.266 second. The assembly line performance is 74.97 percent. To reduce a cycle time in workstation, an assembly line was balanced in order to meet the required production rate. The results showed that one workstation and 2 workers could be eliminated. Labor savings were 8.3 percent and takt time was reduced to 1.20 second. Productivity was increased by 5.2 percent. Moreover, the assembly line performance was increased to 84.93 percent.